Silencing an N-Acyltransferase-Like involved in lignin biosynthesis in nicotiana attenuata dramatically alters herbivory-induced phenolamide metabolism - Gaquerel, Emmanuel; Kotkar, Hemlata M.; Onkokesung, Nawaporn; Galis, Ivan; Baldwin, Ian T. (PLOS ONE, 2013)
In a transcriptomic screen of Manduca sexta-induced N-acyltransferases in leaves of Nicotiana attenuata, we identified an N-acyltransferase gene sharing a high similarity with the tobacco lignin-biosynthetic hydroxycinnamoyl-CoA:shikimate/quinate hydroxycinnamoyl transferase (HCT) gene whose expression is controlled by MYB8, a transcription factor that regulates the production of phenylpropanoid polyamine conjugates (phenolamides, PAs). To evaluate the involvement of this HCT-like gene in lignin production as well as the resulting crosstalk with PA metabolism during insect herbivory, we transiently silenced (by VIGs) the expression of this gene and performed non-targeted (UHPLC-ESI/TOF-MS) metabolomics analyses. In agreement with a conserved function of N. attenuata HCT-like in lignin biogenesis, HCT-silenced plants developed weak, soft stems with greatly reduced lignin contents. Metabolic profiling demonstrated large shifts (up to 12% deregulation in total extracted ions in insect-attacked leaves) due to a large diversion of activated coumaric acid units into the production of developmentally and herbivory-induced coumaroyl-containing PAs (N′,N′′-dicoumaroylspermidine, N′,N′′-coumaroylputrescine, etc) and to minor increases in the most abundant free phenolics (chlorogenic and cryptochlorogenic acids), all without altering the production of well characterized herbivory-responsive caffeoyl- and feruloyl-based putrescine and spermidine PAs. These data are consistent with a strong metabolic tension, exacerbated during herbivory, over the allocation of coumaroyl-CoA units among lignin and unusual coumaroyl-containing PAs, and rule out a role for HCT-LIKE in tuning the herbivory-induced accumulation of other PAs. Additionally, these results are consistent with a role for lignification as an induced anti-herbivore defense.
Gesehen am 18.05.2017